After the insanity defense: when the acquitted return to the community - Shaw, Matthew F. (Criminal justice recent scholarship, 2007)
Studying recidivism -- NGRI research programs -- Conducting a study -- Findings from the study -- Policy and research implications -- Appendix A: Additional NGRI research programs -- Appendix B: Adult needs and strengths assessment -- References -- Index